Numerical Study of Concentric Brace Equipped with the Eccentric Elements for Strengthening Buildings - Asadullah Attal; Mohammad Ali Kafi (Journal of Rehabilitation in Civil Engineering)
Concentric bracing with ease of design and execution and low construction cost represents the widely used system for resisting the structures to lateral forces. The diverse lateral load-bearing system has a variety of types, characterized by its main performance properties as bearing capacity, stiffness, performance ductility, and energy dissipation. Studies revealed that the brace system is a valuable option for retrofitting existing steel and reinforced concrete structures. However, the bracing system suffers a weakness called axial buckling of the brace under critical compressive load, reducing bearing capacity and interrupting energy dissipation. To address this imperfection and induce the seismic response of the concentrically braced frames, several methods proposed to optimize the performance of concentric braces as; using ductile connections, incorporating shear dissipators, hydraulic or mechanical dampers, frictional dissipators, and restrained braces to avoid buckling. Therefore, in this study, an innovative geometry of brace-to-frame connection is investigated to enhance the concentric brace's performance. The local dissipative fuse system is used to connect the steel channels with the gusset plate at one or both ends and at the time of the earthquake the dissipator yields before the brace buckles and forms a flexible plastic hinge, consuming a significant amount of earthquake energy. Similar studies have been performed earlier but the valuable tensional capacity of the braces was affected. Thus, the innovative method aims to maintain the tensional capacity of the brace in addition to buckling prevention and energy dissipation. Also, the dissipators have a post-earthquake ability to easily provide and replace. Consequently, the numerical work performed in this study effectively prevents buckling, and enhanced energy dissipation while maintaining the full tensional functionality of the brace.